Perkecambahan Biji Pinang (Areca catechu L.) pada Beberapa Waktu Perendaman Air Kelapa Muda - Defri Yoza; Rosmimi '; Bustami ' (Jurnal Sagu, 2008)
This research aimed to investigate the best soaking time for areca seed in young coconut water to improve its germination. This research was carried out in Jalan Limbungan, Limbungan village Rumbai district, Pekanbaru city. This research started from early March to end of May 2005. The method esed in this research was non factorial of completely randomized design with 3 replications. Parameters in this research were the time germination, germination ability, speed of germination, plumulae length, root length, and dry weight of seed. The seed soaking treatments significantly affected all germination parameters except the root length and the best treatment for araca seed is A4 (24 hours of soaking).